Optimization of biodegradable plastic production on sugar cane molasses in Enterobacter sp. SEL2 - Naheed, Nighat (Sociedade Brasileira de Microbiologia, 2014)
Contaminated environments have a large number of bacteria which can accumulate PHA as their energy reserves. Out of 54 isolated bacterial strains from three groups of contaminated sites 48 were found PHA positive. The sites were grouped on the basis of the type of carbon sources i.e. sugars, fatty acids and much diverse type. Strains MFD5, MFD11, UML3, USL2, SEL2, SEL3, SEL10 and PFW1 produced 69.9 ± 0.29, 75.27 ± 0.45, 65.43 ± 0.1, 72.54 ± 0.27, 76.61 ± 0.28, 61.81 ± 0.05, 71.16 ± 0.09 and 74.92 ± 0.5 percent of PHA to their constant cell weight (CCW) respectively in PHA detection media supplemented with 2% glucose. Molasses, whey, crumbs hydrolysate and palm oil were checked as inexpensive carbon sources. Molasses alone could supply the required nutrients for growth and PHA production. Strain SEL2 produced 47.36 ± 0.45% PHA using 2% molasses at 37 °C and pH 7.0. Upon production optimization the best accumulation (80.95 ± 0.01%) was observed in PHA detection media with 0.2% nitrogen source, 3% molasses, pH 5.0 and 37 °C by the strain SEL2. The overall effect of the presence of increased molasses concentration in the media was positive it increased the accumulation period till 72 h. Enterobacter sp. SEL2 (JF901810) is first time being reported for PHA production.